Photomodulation multiple sessions as a promising preventive therapy for medication-related osteonecrosis of the jaws after tooth extraction in rats - Statkievicz, Cristian [UNESP]; Toro, Luan Felipe [UNESP]; de Mello-Neto, João Martins [UNESP]; de Sá, Daniela Pereira [UNESP]; Casatti, Cláudio Aparecido [UNESP]; Issa, João Paulo Mardegan; Cintra, Luciano Tavares Angelo [UNESP]; de Almeida, Juliano Milanezi [UNESP]; Nagata, Maria José Hitomi [UNESP]; Garcia, Valdir Gouveia [UNESP]; Theodoro, Leticia Helena [UNESP]; Ervolino, Edilson [UNESP] (My University, 2018)
The aim of this study was to evaluate the effects of photobiomodulation (PBM) with multiple sessions of low-level laser on the alveolar repair process of rats with major risk factors for medication-related osteonecrosis of the jaws (MRONJ). Senile rats received 0.45 mL of vehicle (VEH and VEH-PBM) or 0.45 mL of 100 μg/kg zoledronate (ZOL and ZOL-PBM) administrated intraperitoneally every two days during seven weeks. After three weeks of initiation of drug treatment the first lower left molar was extracted. No local treatment was performed in VEH and ZOL. VEH-PBM and ZOL-PBM were submitted to laser irradiation (660 ± 10 nm; 0.035 W; 2.1 J; 60 s) on the extraction site at 0, 2 and 4 days postoperatively. Euthanasia was performed 28 days after tooth extraction. Histological sections of the hemimandible were submitted to histopathological and histomorphometric analysis, as well as to histochemistry for collagen fiber maturation and immunohistochemistry for pro-inflammatory cytokines. In ZOL, general impairment of tissue repair, areas with osteonecrosis, lower newly formed bone tissue (NFBT), smaller amount of mature collagen fibers and increased immunoreactivity for TNFα IL-1β and IL-6 were observed when compared to VEH and VEH-PBM. ZOL-PBM showed significant improvement in some parameters compared to ZOL, such as positive repair tissue, higher NFBT, greater amount of mature collagen fibers, besides TNFα and IL-1β immunoreactivity decrease. Zoledronate treatment severely compromised the tissue repair process of the tooth extraction site in rats with major risk factors for MRONJ. Based on parameters employed in the present study, PBM in multiple sessions can improve the alveolar repair process, constituting a promising preventive therapy to avoid the onset of post-extraction MRONJ.
Keywords: Bisphosphonates; Jaw; Low-level laser therapy; Osteonecrosis; Photobiomodulation